2009
DOI: 10.1111/j.1559-4572.2008.00043.x
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Structural and Functional Changes in the Metabolic Syndrome

Abstract: To test the hypothesis that the cardiac structural and functional abnormalities of the metabolic syndrome (MS) are independent of body mass index (BMI), 160 untreated patients (aged 47+/-1 years [mean +/- SEM], 53% male) underwent 2-dimensional echocardiography and tissue Doppler imaging and evaluation for MS. Participants with MS and controls were similar in age, BMI, and ejection fraction, but those with MS had greater left ventricular relative wall thickness (RWT) (0.43+/-0.008 vs 0.39+/-0.005, P<.001), red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 35 publications
3
18
0
1
Order By: Relevance
“…MPI, which is detected by TDI, reflects both systolic and diastolic dysfunction. As some previous clinical studies, the MPI was significantly higher in the MetS groups than control subjects in our study (6, 22, 24, 25). …”
Section: Discussionsupporting
confidence: 85%
“…MPI, which is detected by TDI, reflects both systolic and diastolic dysfunction. As some previous clinical studies, the MPI was significantly higher in the MetS groups than control subjects in our study (6, 22, 24, 25). …”
Section: Discussionsupporting
confidence: 85%
“…We cannot provide a definitive explanation for this fact. However, some studies have reported that obesity with metabolic syndrome can be associated with diastolic dysfunction and abnormalities in left ventricular relaxation (17,28,48), although the described abnormal diastolic function is not unanimously reported (52). Thus it is possible to hypothesize that impairment in ventricular diastolic function hampered the normal diastolic filling in subjects with OMS, and this fact in turn resulted in the impaired VFR response.…”
Section: Discussionmentioning
confidence: 91%
“…The pulse pressure, pulse wave velocity and echocardiographic surrogate measurements of arterial stiffness increase with age and in certain disease states, indicating that they themselves are associated with increased cardiovascular risks, including that of hypertension, diabetes mellitus, hyperlipidemia, obesity and end-stage renal failure (17)(18)(19)(20). However, the state of arterial elasticity in subjects with prediabetes has also received little attention.…”
Section: Discussionmentioning
confidence: 99%